1999
DOI: 10.1046/j.1365-2958.1999.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

The macrolide–ketolide antibiotic binding site is formed by structures in domains II and V of 23S ribosomal RNA

Abstract: SummaryThe macrolide antibiotic erythromycin interacts with bacterial 23S ribosomal RNA (rRNA) making contacts that are limited to hairpin 35 in domain II of the rRNA and to the peptidyl transferase loop in domain V. These two regions are probably folded close together in the 23S rRNA tertiary structure and form a binding pocket for macrolides and other drug types. Erythromycin has been derivatized by replacing the L-cladinose moiety at position 3 by a keto group (forming the ketolide antibiotics) and by an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
215
1
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(241 citation statements)
references
References 32 publications
18
215
1
7
Order By: Relevance
“…However, the conclusions about the contribution of the 11,12 side chain to the drug activity should be drawn only cautiously. Although original studies suggested that interactions of the side chain of ketolides with A752 in the loop of helix 35 in 23S rRNA significantly contribute to the drugs' affinity (9,17,49), more recent genetic studies questioned that conclusion because mutations at and around A752 or at U2609, with which the side chains interact, had only a minor effect upon drug inhibitory action (14,21,30,49). In agreement with these observations, the additional interaction afforded by the extended side chains of telithromycin and CEM-101 or, for that matter, the fluorine atom at the C-2 position of the CEM-101 lactone did not translate in our study to an improved ability of either of the ketolides compared with that of azithromycin in inhibiting erythromycin binding to the ribosome (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the conclusions about the contribution of the 11,12 side chain to the drug activity should be drawn only cautiously. Although original studies suggested that interactions of the side chain of ketolides with A752 in the loop of helix 35 in 23S rRNA significantly contribute to the drugs' affinity (9,17,49), more recent genetic studies questioned that conclusion because mutations at and around A752 or at U2609, with which the side chains interact, had only a minor effect upon drug inhibitory action (14,21,30,49). In agreement with these observations, the additional interaction afforded by the extended side chains of telithromycin and CEM-101 or, for that matter, the fluorine atom at the C-2 position of the CEM-101 lactone did not translate in our study to an improved ability of either of the ketolides compared with that of azithromycin in inhibiting erythromycin binding to the ribosome (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Various ketolides differ from CEM-101 in the chemical nature of the alkyl-aryl side chain and the site of its attachment to the lactone scaffold. Nevertheless, in the RNA probing experiments, all these drugs afford a nearly complete protection of A752 in the E. coli ribosome from chemical modification (9,17,48,49), indicating that the interaction of the alkyl-aryl side chain with the A752-U2609 base pair is important for binding of a range of clinically relevant ketolides to the ribosome. Despite a generally similar orientation of the side chains of CEM-101 and telithromycin, the variation in their chemical structures produces an important difference in the mode of binding.…”
Section: Vol 54 2010 Interaction Of a New Fluoroketolide With The Rmentioning
confidence: 99%
See 1 more Smart Citation
“…A2058 and nucleotides that are nearby in the primary and higher-order rRNA structures are involved in the binding of erythromycin and other MLS B antibiotics (32)(33)(34)(35). Mutations at these nucleotides or modification by Erm MTases confer antibiotic resis tance (36)(37)(38), presumably by reducing the strength of the drug-rRNA interaction (39).…”
Section: S Rrna Methyltransferasementioning
confidence: 99%
“…8 This results in tighter binding to ribosomes and imparts some activity against methylated ribosomes in some species. 9,10 The study of the high-resolution X-ray co-crystal structures has revealed that macrolides bind at the entrance to the peptide tunnel in the 23S rRNA, and the cladinose group in their structures is located at and fits with the cavity formed by G2505, C2610 and C2611 in domain V. 11 On the basis of the results of the X-ray co-crystal structure study, many new derivatives of macrolides for the effective management of erythromycin resistance have been investigated by different research groups. 12 These investigations have led to the discovery of 4 00 -modified macrolide derivatives such as CP-544372 13 and A-60565 14 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%